Study on anti-bacterial potentials of some Malaysian brown seaweeds - Jaswir, Irwandi; Tawakalit Tope, Asiyanbi-Hammed; Ahmad Raus, Raha; A. Monsur, Hammed Ademola; Ramli, Nazaruddin (Elsevier Inc., 2014)
With increasing in emergence of resistance pathogenic microorganisms to majority of antibiotics, there is an urgent and continuous need for exploring and developing cheaper and effective plant based drugs with better bioactive potential and least side effects. Bioactive extracts from four species of brown seaweeds (Sargassum plagyophillum, Sargassum flavellum, Padina australis and Sargassum binderi) of Malaysia origin were tested in vitro for their anti-bacterial activities against gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and gram negative bacteria (Pseudomonas aeruginosa and Escherichia coli). Four solvents (methanol, acetone, ethyl acetate and chloroform) were used during the preliminary screening stage to obtain crude extracts. None of the crude extracts displayed antimicrobial activity against the gram negative bacteria while the gram positive bacteria were inhibited. Methanol extract of S. plagyophillum was the best in terms of yield (4.72%) and antimicrobial activity with inhibition zone of 12 mm against B. subtilis. Chloroform fraction gave highest inhibition zone of 17 mm against B. subtilis. Hence, the result from this work showed that S. plagyophillum has the potential for antimicrobial drug production.